High-purity carbon-coated sodium iron pyrophosphate and integrated preparation method thereof and sodium-ion battery
Patent Information
- Application Number
- CN202611320247.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]鉴于上述的分析,本发明实施例旨在提供一种高纯度碳包覆磷酸焦磷酸铁钠及其一体化制备方法和钠离子电池,用以解决现有磷酸焦磷酸铁钠制备工艺冗长、成本高以及煅烧过程磷挥发严重、表面杂相多等问题中的至少一种
1、本发明的制备方法采用磷酸铁湿滤饼直接投料进入配浆工序,全程无需制备磷酸铁固体中间产物,省去制备磷酸铁粉体成品所需的干燥、预煅烧、破碎、转运等6道以上工序,生产周期大大缩短,全流程仅一次固体产出,减少了杂质的引入,相比于传统两步液相-固相结合法,综合生产能耗降低,生产成本大幅降低,实现了从硫酸亚铁原料到NFPP成品的全链路一体化连续生产。
Smart Images

Figure CN122897383A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery materials technology, and in particular to a high-purity carbon-coated sodium iron pyrophosphate, its integrated preparation method, and a sodium-ion battery. Background Technology
[0002] Sodium iron pyrophosphate (NFPP) is a typical iron-based polyanionic sodium-ion cathode material with a theoretical specific capacity of 128 mAh / g and an average operating voltage of about 3.2V. It has core advantages such as three-dimensional sodium-ion diffusion channels, stable crystal structure, high thermal safety, abundant raw material reserves and low cost, making it one of the most promising sodium-ion battery cathode materials for industrialization.
[0003] Currently, the preparation process of NFPP mainly adopts a two-step liquid-solid combined method: first, ferric phosphate powder is prepared through co-precipitation, drying, and pre-calcination; then, the ferric phosphate powder is added again with a sodium source, pyrophosphate, and carbon source, followed by mixing, spray drying, and high-temperature calcination to obtain the NFPP product. This route has the following core problems: (1) The process is lengthy and the overall cost is high: two independent production lines are required, which include multiple drying, calcination and crushing processes. The production cycle is more than 20 hours and the overall energy consumption is high. The hard agglomerates formed by drying iron phosphate are difficult to disperse completely, and uneven mixing of raw materials leads to high impurity content after calcination. (2) Severe phosphorus volatilization during calcination and numerous surface impurities: During high-temperature calcination, phosphorus on the surface of the particles is easily volatilized and lost, leading to phosphorus deficiency and the formation of inert impurities such as NaFePO4 and Fe2O3, which deteriorates the material's first-cycle coulombic efficiency and cycle stability. Existing external phosphorus compensation processes require the introduction of additional phosphine gas or the placement of additional phosphorus sources in the kiln, which is complex, poses high safety risks, and results in poor uniformity of phosphorus compensation. Summary of the Invention
[0004] Based on the above analysis, the present invention aims to provide a high-purity carbon-coated sodium pyrophosphate, an integrated preparation method thereof, and a sodium-ion battery, in order to solve at least one of the problems of the existing sodium pyrophosphate preparation process being lengthy and costly, as well as severe phosphorus volatilization and numerous surface impurities during the calcination process.
[0005] On one hand, the present invention provides an integrated preparation method for high-purity carbon-coated iron pyrophosphate sodium, comprising: S1, preparing ferric phosphate wet filter cake; S2, Preparation of slurry: Disperse the wet filter cake of ferric phosphate into a solvent to form a slurry; add organophosphonic acid to the slurry; then add pyrophosphate source to the slurry; then add phosphorus source, sodium source and carbon source to the slurry to obtain a uniform mixed slurry; S3, spray-dry the mixed slurry to obtain the precursor; S4, the precursor is calcined in an inert atmosphere to obtain carbon-coated iron pyrophosphate sodium.
[0006] Furthermore, the amount of organophosphonic acid added is 0.3wt% to 1.0wt% of the total solid phase mass in the slurry formed by dispersing the ferric phosphate wet filter cake.
[0007] Furthermore, organophosphonic acids include at least one of hydroxyethylidene diphosphonic acid and aminotrimethylene phosphonic acid.
[0008] Furthermore, the molar amount of pyrophosphate source is 1% to 3% of the total molar amount of phosphorus in the mixed slurry containing ferric phosphate and phosphorus supplement source.
[0009] Furthermore, after adding pyrophosphate, the pH of the slurry is maintained at 2.0~2.5.
[0010] Furthermore, the carbon source includes one or more of glucose and sucrose; Furthermore, the amount of carbon source added is 5wt% to 10wt% of the final product mass.
[0011] Furthermore, in S3, before spray drying the mixed slurry, the mixed slurry is ground until the particle size D50 in the mixed slurry is 0.3~0.5μm.
[0012] Furthermore, in S4, calcination includes: First stage: Heat to an intermediate calcination temperature of 280~320℃ and hold for 1~2 hours; Second stage: Continue to heat up to a calcination temperature of 530~560℃ and hold for 4~5 hours.
[0013] On the other hand, the present invention also provides a high-purity carbon-coated iron pyrophosphate sodium, which is obtained by the above-described integrated preparation method.
[0014] In another aspect, the present invention also provides a sodium-ion battery, wherein the positive electrode material of the sodium-ion battery is high-purity carbon-coated iron pyrophosphate sodium obtained by the above-mentioned integrated preparation method.
[0015] This invention can achieve at least one of the following beneficial effects: 1. The preparation method of the present invention uses ferric phosphate wet filter cake to be directly fed into the slurry preparation process. There is no need to prepare ferric phosphate solid intermediate products throughout the process, which eliminates more than 6 processes such as drying, pre-calcination, crushing and transfer required to prepare ferric phosphate powder finished products. The production cycle is greatly shortened. The entire process only produces solid products once, which reduces the introduction of impurities. Compared with the traditional two-step liquid-solid combination method, the overall production energy consumption is reduced and the production cost is greatly reduced. It realizes the integrated continuous production of the entire chain from ferrous sulfate raw material to NFPP finished product.
[0016] 2. This invention introduces organophosphonic acid as a functional bridge. In the liquid phase, it acts as an interface regulator to assist pyrophosphate in constructing a crystal phase-inducing structure on the surface of iron phosphate particles in situ, preferentially inducing NFPP growth, reducing impurities, and facilitating subsequent low-temperature phase formation and grain refinement. At the same time, in the calcination stage, it acts as a compensating phosphorus source, decomposing to generate phosphorus oxides to achieve in-situ uniform phosphorus atmosphere self-compensation, reducing surface impurities and defects.
[0017] 3. In the preparation method of the present invention, the crystal phase induction and in-situ phosphorus compensation functions of organophosphonic acid are enhanced in both directions. The two work together to significantly improve the crystal phase purity and surface defect suppression of the material, and significantly improve the long cycle stability and rate performance. The performance improvement effect exceeds the improvement effect of single crystal phase induction or single phosphorus compensation.
[0018] 4. The impurity phase content in the carbon-coated iron pyrophosphate sodium of this invention is below 0.8%, which is more than 81% lower than that of the traditional two-step method. When used as a cathode material in sodium-ion batteries, the sodium-ion battery exhibits a discharge specific capacity of over 108.8 mAh / g at 0.1C, a first-cycle coulombic efficiency of over 92.9% at 0.1C, a discharge specific capacity of over 95.6 mAh / g at 10C, and a capacity retention rate of over 93.2% after 1000 cycles at 1C. Furthermore, the integrated preparation method of this invention eliminates the need to produce finished iron phosphate, reducing energy consumption by more than 35% compared to the traditional two-step method.
[0019] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0020] The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of the invention.
[0021] Figure 1 This is an electron microscope image of carbon-coated iron sodium pyrophosphate according to Example 2 of the present invention.
[0022] Figure 2 The image shows the XRD pattern of carbon-coated iron pyrophosphate sodium according to Example 2 of the present invention. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the present invention clearer, exemplary embodiments of the present invention will be described below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. For clarity and brevity, not all features of actual embodiments are described in the specification.
[0024] An embodiment of the present invention provides a method for preparing high-purity carbon-coated iron pyrophosphate sodium, comprising: S1, preparing ferric phosphate wet filter cake; S2, Slurry preparation: Disperse the wet filter cake of ferric phosphate in a solvent to form a slurry; add organophosphonic acid to the slurry; then add pyrophosphate to the slurry so that, under the interfacial regulation of organophosphonic acid, pyrophosphate reacts with the unsaturated Fe on the surface of ferric phosphate. 2+ Coordination and in-situ construction of crystal phase-induced structures to induce subsequent growth of sodium iron pyrophosphate crystal phases; then, phosphorus source, sodium source and carbon source are added to the slurry to obtain a uniform mixed slurry; S3, spray-dry the mixed slurry to obtain the precursor; S4. The precursor is calcined under an inert atmosphere to obtain carbon-coated iron pyrophosphate sodium.
[0025] The preparation method of this invention uses ferric phosphate wet filter cake to be directly fed into the slurry preparation process. There is no need to prepare ferric phosphate solid intermediate products throughout the process, which eliminates more than 6 processes such as drying, pre-calcination, crushing, and transfer required to prepare ferric phosphate powder finished products. The production cycle is greatly shortened. The entire process only produces solid products once, which reduces the introduction of impurities. Compared with the traditional two-step liquid-solid combination method, the overall production energy consumption is reduced and the production cost is greatly reduced. It realizes the integrated continuous production of the entire chain from ferrous sulfate raw material to NFPP finished product, and is suitable for fully enclosed continuous large-scale production.
[0026] Because NFPP phase formation requires complex reactions such as phosphate condensation and pyrophosphate structure construction, directly using a wet filter cake feeding process will result in increased impurity content and cannot solve the industry pain point of severe phosphorus volatilization. Therefore, embodiments of this invention introduce organophosphonic acid as a functional bridge. In the liquid phase, it acts as an interface regulator, assisting pyrophosphate in situ construction of a crystal phase-inducing structure on the surface of iron phosphate particles, preferentially inducing NFPP growth and reducing impurities. Simultaneously, in the calcination stage, it acts as a compensating phosphorus source, decomposing to generate phosphorus oxides to achieve in-situ uniform phosphorus atmosphere self-compensation, reducing surface impurities and defects. High-purity carbon-coated iron pyrophosphate sodium is directly obtained through only one spray drying and one inert atmosphere calcination.
[0027] Therefore, the embodiments of the present invention directly feed the slurry with iron phosphate wet filter cake and simultaneously introduce organic phosphonic acid for two-stage synergistic regulation, thereby reducing the impurity phase content of the NFPP system and improving the long-cycle stability and rate performance of sodium-ion batteries. This simultaneously achieves process simplification, cost reduction, and improvement of NFPP crystal phase purity and performance.
[0028] Specifically, the embodiments of this invention use the same organophosphonic acid as a bifunctional additive, simultaneously undertaking the dual functions of liquid-phase interface regulation and calcination of phosphorus source precursors, achieving dual effects with a single agent without the need to introduce additional additives. On the one hand, organophosphonic acid can act as an interface regulator in the liquid phase stage, assisting trace amounts of pyrophosphate ions to construct a crystal phase-inducing structure in situ on the surface of iron phosphate particles, inducing preferential growth of subsequent NFPP crystal phases. This avoids the dissolution and failure of solid pyrophosphate seed crystals in the pickling slurry, reduces the energy barrier of the phase formation reaction, and facilitates a subsequent reduction in the phase formation temperature. This fundamentally reduces the amount of high-temperature phosphorus volatilization, lowers the phosphorus compensation pressure, achieves low-temperature crystal phase induction, and refines the grains. On the other hand, in the calcination stage, it acts as a phosphorus source, decomposing to generate phosphorus oxides to achieve in-situ phosphorus compensation. This eliminates the surface phosphorus deficiency defects in the phase formation process, ensures the full utilization of the crystal phase induction effect, avoids surface impurities from damaging the continuity of the crystal nucleus template, and avoids the defects of complex and unsafe exogenous phosphorus compensation processes.
[0029] In the embodiments of the present invention, the crystal phase induction and in-situ phosphorus compensation functions of organophosphonic acid are enhanced in both directions. The two work together to significantly improve the crystal phase purity and surface defect suppression of the material, and significantly improve the long-cycle stability and rate performance. The performance improvement effect exceeds the improvement effect of single crystal phase induction or single phosphorus compensation.
[0030] According to some embodiments of the present invention, the dry basis solid content of the ferric phosphate wet filter cake prepared in step S1 is 30wt%~40wt%, for example 30wt%, 32wt%, 35wt%, 38wt%, or 40wt%. The dry basis Fe / P molar ratio is 1:1.01~1.03, for example 1:1.01, 1:1.02, or 1:1.03. The dry basis sulfur content is ≤100ppm. In the embodiments of the present invention, the ferric phosphate wet filter cake is directly fed into the slurry, without drying, pre-calcination, or crushing treatment throughout the process. No solid ferric phosphate product is produced; the wet filter cake directly enters the next process, simplifying the process flow and facilitating the integrated continuous preparation of NFPP.
[0031] According to some embodiments of the present invention, step S2 specifically includes the following steps: S21, mix the wet filter cake of ferric phosphate obtained in S1 with the solvent and stir until the wet filter cake of ferric phosphate is completely dispersed to form a slurry; S22, add organophosphonic acid to the above slurry and stir to mix; S23, add pyrophosphate source to the above slurry and stir to mix; S24, according to the stoichiometric ratio of Na4Fe3(PO4)2(P2O7), add phosphorus source, sodium source and carbon source to the slurry, and stir to obtain a uniform mixed slurry.
[0032] If sodium pyrophosphate seed crystals are added directly to lower the phase formation temperature, sodium pyrophosphate is easily dissolved and ineffective in acidic ferric phosphate slurry, failing to stably exert its seed-inducing effect. Therefore, embodiments of the present invention add organophosphonic acid before adding pyrophosphate. Organophosphonic acid, as an interface modifier, can optimize the surface charge distribution of ferric phosphate particles and reduce the interfacial hydrogen ion activity. Based on this, pyrophosphate is added, and under the interfacial modulating effect of organophosphonic acid, trace amounts of pyrophosphate preferentially react with the unsaturated Fe on the surface of the ferric phosphate particles. 3+ Coordination and in-situ generation of covalently bonded ≡Fe-O-P2O7 surface structure units serve as two-dimensional molecular templates to induce preferential growth of the subsequent NFPP crystal phase, reducing the energy barrier of the phase formation reaction and facilitating a reduction in the calcination temperature.
[0033] In step S21, the wet filter cake of ferric phosphate is mixed with a solvent, and the solid mass fraction in the slurry is adjusted to 20%~25%, for example, 20%, 21%, 22%, 23%, 24%, or 25%. The solvent used is deionized water. Then, stirring is performed at a speed of 200~400 rpm for 10~20 minutes.
[0034] In step S22, organophosphonic acid is added to the slurry, and the temperature is controlled at 30~40℃ (e.g., 30℃, 32℃, 35℃, 38℃, 40℃). Stirring is continued for 5~15 minutes, so that the organophosphonic acid is anchored on the surface of iron phosphate particles through PO-Fe coordination bonds, thereby activating the surface hydroxyl groups.
[0035] The organophosphonic acid includes at least one of hydroxyethylidene diphosphonic acid and aminotrimethylene phosphonic acid. In the embodiments of the present invention, the organophosphonic acid acts as an interface regulator, which can optimize the surface charge distribution of iron phosphate particles, reduce the interfacial hydrogen ion activity, and provide reaction sites for subsequent in-situ coordination of pyrophosphate.
[0036] The amount of organophosphonic acid added is 0.3wt% to 1.0wt% of the total solid phase mass in the slurry formed by dispersing the ferric phosphate wet filter cake, for example, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%.
[0037] In step S23, the pyrophosphate source can be sodium pyrophosphate or pyrophosphate. The total molar amount of pyrophosphate source is 1% to 3% of the total molar amount of phosphorus in the mixed slurry containing ferric phosphate and phosphorus supplement source, for example, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%.
[0038] In step S23, after introducing pyrophosphate into the slurry, the pH of the slurry is adjusted to 2.0~2.5, for example, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5. The temperature is controlled at 30~40℃ (for example, 30℃, 32℃, 35℃, 38℃, 40℃), and stirring is continued for 15~30min, for example, 15min, 20min, 25min, 30min.
[0039] In embodiments of the present invention, by adjusting the pH of the slurry after adding pyrophosphate, a stable Fe-OP coordination anchoring between the organophosphonic acid and the surface of ferric phosphate can be ensured. In a weakly acidic environment of pH 2.0–2.5, a large number of ≡Fe-OH hydroxyl active sites are retained on the surface of the ferric phosphate particles; the organophosphonic acid undergoes moderate dissociation, and the oxygen atoms of the phosphonic acid groups undergo ligand exchange reactions, removing surface hydroxyl groups and forming Fe-OP covalent bonds through internal spherical coordination, firmly anchoring them to the particle surface. If pH > 2.5, the OH groups in the system... - Increase, Fe 3+ It easily forms flocculent precipitates of ferric hydroxide, which block the surface coordination sites. Organophosphonic acids mainly rely on physical adsorption, resulting in a significant decrease in anchoring strength, and the subsequent formation of Fe-OC carbon-coated covalent interfaces is impossible. If pH < 2.0, the acidity is too strong, the phosphonic acid groups are excessively protonated, the coordination ability is significantly weakened, and the organophosphonic acid only plays a dispersing role, losing its dual functions of interface regulation and calcined phosphorus compensation precursor.
[0040] Specifically, after adding pyrophosphate and stirring thoroughly, an online pH electrode is used for real-time monitoring. When the pH exceeds the range of 2.0 to 2.5, dilute phosphoric acid or dilute ammonia is added dropwise to adjust the pH and maintain it within the range of 2.0 to 2.5. Specifically, when the pH is > 2.5, dilute phosphoric acid is slowly added dropwise, with small amounts added multiple times while stirring. After each addition, the pH of the slurry is retested after stirring for 1 to 3 minutes until the pH is adjusted to 2.0 to 2.5. When the pH is < 2.0, a small amount of dilute ammonia is added dropwise to adjust the pH back to 2.0 to 2.5.
[0041] In embodiments of the present invention, the temperature is controlled at 30-40°C in steps S22 and S23, that is, the slurry system is kept at a constant temperature of 30-40°C during the stirring reaction. Under this temperature condition, on the one hand, the ligand exchange between organophosphonic acid and the trivalent iron on the surface of ferric phosphate can be accelerated to form a uniform and stable Fe-OP coordination anchoring structure; on the other hand, the high-temperature hydrolysis and bond breaking of pyrophosphate can be suppressed, ensuring that it constructs crystal phase induction units at the particle interface with an intact structure; at the same time, it avoids the high-temperature induction of Fe 3+ Hydrolysis produces iron hydroxide impurities, which stabilize the pH detection accuracy and rheological state of the slurry, prevent premature deterioration of the carbon source, and improve the uniformity of precursor components and batch preparation stability.
[0042] In step S24, according to the stoichiometric ratio of Na4Fe3(PO4)2(P2O7), phosphorus source, sodium source and carbon source are added to the slurry to adjust the solid mass fraction in the slurry to 40%~50% (e.g. 40%, 42%, 45%, 48%, 50%), and stirring is continued for 20~40 minutes to obtain a uniform mixed slurry.
[0043] The phosphorus source includes sodium dihydrogen phosphate. The amount of phosphorus source added is calculated according to the stoichiometric ratio of sodium iron pyrophosphate. Specifically, the total molar amount of phosphorus required for product phase formation is determined based on the total amount of iron, and the phosphorus content in iron phosphate and pyrophosphate is deducted to obtain the amount of phosphorus source to be added.
[0044] Sodium sources include one or more of anhydrous sodium carbonate and sodium acetate.
[0045] The carbon source includes one or more of glucose and sucrose. The amount of carbon source added is 5 wt% to 10 wt% of the final product mass, for example, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%. By controlling the amount of carbon source added, this invention can provide sufficient carbon source for the coating of the carbon layer on the NFPP, enabling it to form a continuous and stable conductive network, while avoiding an excessively thick carbon layer that would hinder sodium ion transport.
[0046] According to some embodiments of the present invention, in S3, before spray drying the mixed slurry, the mixed slurry is ground until the particle size D50 in the mixed slurry is 0.3~0.5μm, for example, 0.3μm, 0.35μm, 0.4μm, 0.45μm, or 0.5μm.
[0047] According to some embodiments of the present invention, when spray drying the mixed slurry, the inlet air temperature is controlled at 170~180℃ and the outlet air temperature is controlled at 85~95℃ to obtain a spherical precursor. For example, the inlet air temperatures are 170℃, 171℃, 172℃, 173℃, 174℃, 175℃, 176℃, 177℃, 178℃, 179℃, and 180℃; and the outlet air temperatures are 85℃, 86℃, 87℃, 88℃, 89℃, 90℃, 91℃, 92℃, 93℃, 94℃, and 95℃.
[0048] It should be noted that in the precursor of this invention, organophosphonic acid is distributed on the surface and inside of the particles, providing a phosphorus source for phosphorus compensation in the subsequent calcination stage.
[0049] According to some embodiments of the present invention, in S4, the entire process of dehydration, phosphate condensation, sodication, in-situ phosphorus compensation, and carbon coating is completed simultaneously in a single calcination. Specifically, the precursor can be calcined in an inert atmosphere using a staged calcination method. The inert atmosphere is nitrogen or argon. The calcination specifically includes the following stages: First stage: Heat to an intermediate calcination temperature of 280~320℃ and hold for 1~2 hours to remove water of crystallization and residual ammonium salts, pre-carbonize the carbon source, and begin the initial decomposition of organophosphonic acid; Second stage: Continue to heat to a calcination temperature of 530~560℃ and hold for 4~5 hours to complete crystal growth and carbon coating.
[0050] In the first stage, the heating rate is 1~2℃ / min, for example, 1℃ / min, 1.2℃ / min, 1.5℃ / min, 1.8℃ / min, or 2℃ / min. For example, the intermediate calcination temperature can be 280℃, 285℃, 290℃, 295℃, 300℃, 305℃, 310℃, 315℃, or 320℃; the holding time is 1h, 1.2h, 1.5h, 1.8h, or 2h.
[0051] In the second stage, the heating rate is 2~3℃ / min, for example, 2℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min, or 3℃ / min. For example, the calcination temperatures are 530℃, 535℃, 540℃, 545℃, 550℃, 555℃, or 560℃; the holding times are 4h, 4.2h, 4.5h, 4.8h, or 5h.
[0052] After the second stage of heat preservation is completed, the material is naturally cooled to room temperature, and after being discharged, it is broken up and sieved to obtain carbon-coated iron pyrophosphate sodium.
[0053] The formation of NFPP requires the dehydration condensation of phosphate ions to generate pyrophosphate ions. The solid-phase reaction has a high energy barrier, requiring conventional calcination temperatures above 620°C and holding times of 8-10 hours. High temperatures easily lead to abnormal grain growth, resulting in poor rate performance of the material. In contrast, the embodiments of this invention introduce organophosphonic acid and pyrophosphate ions in the liquid phase stage, constructing a pyrophosphate-induced structure in situ at the wet interface. This reduces the NFPP formation temperature from 620°C to 530-560°C and shortens the holding time by 50%, achieving low-temperature formation. This fundamentally reduces high-temperature phosphorus volatilization and lowers phosphorus compensation pressure. Simultaneously, low-temperature formation effectively inhibits abnormal grain growth, stabilizing the primary grain size of the product at 50-100 nm, thereby significantly improving the rate performance of sodium-ion batteries.
[0054] Furthermore, organophosphonic acids completely decompose to generate phosphorus oxides (P2O5) during the calcination stage, forming a trace amount of local phosphorus atmosphere around the particles. This compensates for the surface phosphorus volatilization during the calcination process in situ, inhibits the formation of phosphorus-deficient impurity phases, and eliminates the need for additional phosphorus sources or hazardous gases, making the process simple and safe. Moreover, the local phosphorus atmosphere around the particles is uniformly distributed, which can completely offset the surface phosphorus volatilization during the calcination process. The content of surface NaFePO4 and Fe2O3 impurity phases is reduced by more than 90%, and the overall purity of the main phase is increased to more than 99.3%.
[0055] According to some embodiments of the present invention, in step S1, a wet filter cake of ferric phosphate is prepared using a co-precipitation method. Specifically, S1 includes the following steps: S11, Solution preparation: Prepare ferrous sulfate solution and diamine hydrogen phosphate solution; S12, Oxidation reaction: Hydrogen peroxide solution is slowly added dropwise to ferrous sulfate solution under stirring. The temperature of ferrous sulfate solution is controlled by water bath during the dropwise addition process. After the dropwise addition is completed, stirring is continued until ferrous sulfate is completely oxidized to obtain ferrous sulfate solution. S13, coprecipitation reaction: The ferric sulfate solution is heated at a constant temperature, and a diamine hydrogen phosphate solution and ammonia are added dropwise to the ferric sulfate solution simultaneously; after the addition is completed, the temperature is raised to the reaction temperature and kept at the temperature for aging to allow the crystals to grow; S14, Filtration and washing: After the reaction is complete, the slurry is filtered and washed to obtain a wet filter cake of ferric phosphate.
[0056] In step S11, when preparing the ferrous sulfate solution, ferrous sulfate is first dissolved in deionized water to form an initial solution. Then, reduced iron powder is added and the solution is heated and stirred to remove free ferric iron and heavy metal impurities from the initial solution. Finally, the solution is vacuum filtered to obtain a light green, clear ferrous sulfate solution. The concentration of the initial solution is 0.8–1.2 mol / L, for example, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, or 1.2 mol / L. The amount of reduced iron powder added is 0.3%–0.5% of the mass of ferrous sulfate, for example, 0.3%, 0.35%, 0.4%, 0.45%, or 0.5%. The heating temperature after adding the iron powder is 35–45°C, and the stirring time is 0.8–1.2 h.
[0057] In step S11, the concentration of the prepared diamine hydrogen phosphate solution is 0.8~1.2 mol / L.
[0058] In step S12, the molar amount of hydrogen peroxide added is 52% to 55% of the ferrous ions in the ferrous sulfate solution, for example, 52%, 53%, 54%, or 55%. The concentration of the hydrogen peroxide solution is 30 wt%.
[0059] In step S12, the hydrogen peroxide solution is added dropwise over a period of 30–60 minutes, for example, 30, 40, 50, or 60 minutes. During the addition, the water bath temperature is controlled within the range of 25–40°C to regulate the reaction process and ensure the reaction proceeds safely and efficiently. After the hydrogen peroxide solution addition is complete, stirring continues for another 20–40 minutes.
[0060] In step S13, the isothermal heating temperature of the ferric sulfate solution is 40~50℃, for example, 40℃, 42℃, 45℃, 48℃, 50℃.
[0061] In step S13, the molar ratio of diamine hydrogen phosphate to ferric sulfate is 1.02 to 1.06:1, for example, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, preferably 1.03:1 to 1.05:1.
[0062] In step S13, the total time for adding the diamine hydrogen phosphate solution and ammonia is 1.5~2 hours, for example, 1.5 hours, 1.8 hours, or 2 hours, and the final pH of the reaction is strictly controlled to be 2~2.5. The ammonia used is 25 wt% ammonia, and the ammonia is not added in a fixed amount but is added quantitatively as a pH adjuster.
[0063] In step S13, after the diamine hydrogen phosphate solution is added dropwise, the temperature is raised to the reaction temperature, which is 75~80℃, and the aging time is 1.5~2.5h. For example, the reaction temperature is 75℃, 78℃, and 80℃, and the aging time is 1.5h, 2h, and 2.5h, respectively.
[0064] In step S14, the slurry after the reaction is completed is filtered and washed repeatedly with deionized water at 70~80℃ until the sulfate content in the filtrate is ≤100ppm, thus obtaining a wet filter cake of ferric phosphate dihydrate.
[0065] An embodiment of the present invention also provides a high-purity carbon-coated iron pyrophosphate sodium phosphate, which is prepared by the above-described integrated preparation method.
[0066] The technical solution of the present invention will be further illustrated below with specific embodiments.
[0067] Example 1 This embodiment provides an integrated preparation method for high-purity carbon-coated iron pyrophosphate sodium, including: S1, co-precipitation to prepare ferric phosphate dihydrate wet filter cake: S11, ferrous sulfate heptahydrate was prepared into a 1.0 mol / L ferrous sulfate solution with deionized water, and reduced iron powder accounting for 0.4% of the mass of ferrous sulfate heptahydrate was added. The mixture was stirred at 40℃ for 1 h and then vacuum filtered to obtain a light green clear filtrate; diammonium hydrogen phosphate was prepared into a 1.0 mol / L diammonium hydrogen phosphate aqueous solution for later use. S12, place the ferrous sulfate filtrate in a reaction vessel, control the temperature in a water bath at 25~40℃, and slowly add 30wt% hydrogen peroxide solution dropwise while stirring. The amount of hydrogen peroxide added is 55% of the ferrous ions. The addition time is 50min. After the addition is complete, continue stirring for 30min until the ferrous ions are completely oxidized to obtain ferrous sulfate solution. S13, ferric sulfate solution was kept at a constant temperature of 45℃, and diammonium hydrogen phosphate solution and 25wt% ammonia water were added dropwise simultaneously. The molar ratio of diammonium hydrogen phosphate to iron in ferric sulfate was 1.04:1. The pH of the reaction endpoint was strictly controlled to be 2.0~2.5 by adding ammonia water dropwise. The total dropwise addition time was 1.5h. After the dropwise addition was completed, the temperature was raised to 75℃ and kept at this temperature for 2h to allow the crystals to grow. S14. After the reaction is complete, the slurry is filtered and washed repeatedly with 70℃ deionized water until the sulfate content in the filtrate is ≤100ppm, thus obtaining a wet filter cake of ferric phosphate dihydrate.
[0068] The dry basis solid content of the ferric phosphate wet filter cake in this embodiment is 35 wt%, the dry basis Fe / P molar ratio is 1:1.02, and the dry basis sulfur content is ≤100 ppm. Due to the loss of a small amount of phosphate ions with the washing wastewater during the co-precipitation reaction, and the possibility that some phosphate ions may not have fully participated in the precipitation reaction, the actual phosphorus content in the final wet filter cake is slightly lower than the feed ratio of 1:1.04.
[0069] The test method for the solid content of wet filter cake of ferric phosphate is as follows: a certain mass of wet filter cake (m0) is weighed, dried in an oven at 105℃ until constant weight, and the mass of the dry material (m1) is weighed; the solid content of filter cake is calculated as m1 / m0 × 100%. The test method for the sulfur content on a dry basis is as follows: the dried ferric phosphate powder is taken, and the sulfur content is tested using an inductively coupled plasma optical emission spectrometer (ICP-OES), with the result expressed as a percentage of dry weight.
[0070] S2, pulp preparation: The wet filter cake of ferric phosphate dihydrate of S1 was transferred to a slurry mixing tank, deionized water was added, the solid mass fraction was adjusted to 22%, and the mixture was stirred at 300 rpm for 15 min to disperse it into a slurry; the amount of ferrous sulfate added was 1 mol Fe on a dry basis.
[0071] Aminotrimethylenephosphonic acid (ATMP) was added to the slurry, and the mixture was stirred at 35°C for 10 minutes to activate the surface of the ferric phosphate particles. The amount of ATMP added was 0.3 wt% of the solid phase in the slurry.
[0072] Sodium pyrophosphate was added to the slurry to adjust the pH to 2.2, and the mixture was stirred at 35°C for 25 minutes to construct a crystal-induced structure. The amount of pyrophosphate added was 1% of the total molar amount of phosphorus contained in ferric phosphate and the phosphorus supplement source.
[0073] Sodium dihydrogen phosphate, sodium carbonate, and glucose were added to the slurry to adjust the solid phase mass fraction to 45%, and stirring was continued for 30 minutes. The sodium dihydrogen phosphate was 0.320 mol, the anhydrous sodium carbonate was 0.493 mol, and the glucose monohydrate was 14.6 g, accounting for 7% of the theoretical product mass.
[0074] S3, Grinding and Spray Drying: The mixed slurry obtained in S2 is ground to a particle size D50 = 0.4 μm using a horizontal sand mill; it is then spray dried using a centrifugal spray dryer with an inlet air temperature of 180℃ and an outlet air temperature of 90℃ to obtain the precursor.
[0075] S4, Calcination: The precursor is placed in a tube furnace and protected by argon gas. The temperature is increased and calcined according to the following procedure: the temperature is increased to 300℃ at 1.5℃ / min and held for 1 hour, then the temperature is increased to 560℃ at 2.5℃ / min and held for 5 hours. After the holding period, the material is discharged naturally to obtain carbon-coated iron pyrophosphate sodium phosphate.
[0076] Example 2 This embodiment provides an integrated preparation method for high-purity carbon-coated iron pyrophosphate sodium, including: S1, co-precipitation to prepare ferric phosphate dihydrate wet filter cake, the specific process is the same as in Example 1.
[0077] S2, pulp preparation: The wet filter cake of ferric phosphate dihydrate of S1 was transferred to a slurry mixing tank, deionized water was added, the solid mass fraction was adjusted to 22%, and the mixture was stirred at 300 rpm for 15 min to disperse it into a slurry; the amount of ferrous sulfate added was 1 mol Fe on a dry basis.
[0078] Hydroxyethylidene diphosphonic acid (HEDP) was added to the slurry, and the mixture was stirred at 35°C for 10 minutes to activate the surface of the ferric phosphate particles. The amount of HEDP added was 0.6 wt% of the solid phase in the slurry.
[0079] Sodium pyrophosphate was added to the slurry to adjust the pH to 2.3, and the mixture was stirred at 35°C for 25 minutes to construct a crystal-induced structure. The amount of pyrophosphate added was 2% of the total molar amount of phosphorus in the iron phosphate and phosphorus supplement source.
[0080] Sodium dihydrogen phosphate, sodium carbonate, and glucose were added to the slurry to adjust the solid phase mass fraction to 45%, and stirring was continued for 30 minutes. The composition of sodium dihydrogen phosphate was 0.3067 mol, anhydrous sodium carbonate was 0.487 mol, and glucose monohydrate was 14.6 g, accounting for 7% of the theoretical product mass.
[0081] S3, Grinding and Spray Drying: Same as in Example 1.
[0082] S4, Calcination: The precursor was placed in a tube furnace and calcined under argon protection. The temperature was increased to 300℃ at a rate of 1.5℃ / min and held for 1 hour, then increased to 540℃ at a rate of 2.5℃ / min and held for 4.5 hours. After holding, the material was allowed to cool naturally and discharged to obtain carbon-coated iron pyrophosphate sodium phosphate. Its electron micrograph and XRD pattern are shown below. Figure 1 and Figure 2 As shown.
[0083] Example 3 This embodiment provides an integrated preparation method for high-purity carbon-coated iron pyrophosphate sodium, including: S1, co-precipitation to prepare ferric phosphate dihydrate wet filter cake, the specific process is the same as in Example 1.
[0084] S2, pulp preparation: The wet filter cake of ferric phosphate dihydrate of S1 was transferred to a slurry mixing tank, deionized water was added, the solid mass fraction was adjusted to 22%, and the mixture was stirred at 300 rpm for 15 min to disperse it into a slurry; the amount of ferrous sulfate added was 1 mol Fe on a dry basis.
[0085] Hydroxyethylidene diphosphonic acid (HEDP) was added to the slurry, and the mixture was stirred at 40°C for 10 min to activate the surface of the ferric phosphate particles. The amount of HEDP added was 1.0 wt% of the solid phase in the slurry.
[0086] Sodium pyrophosphate was added to the slurry to adjust the pH to 2.5, and the mixture was stirred at 40°C for 30 minutes to construct a crystal-induced structure. The amount of pyrophosphate added was 3% of the total molar amount of phosphorus contained in ferric phosphate and the phosphorus supplement source.
[0087] Sodium dihydrogen phosphate, sodium carbonate, and glucose were added to the slurry to adjust the solid phase mass fraction to 45%, and stirring was continued for 30 minutes. The sodium dihydrogen phosphate was 0.2933 mol, the anhydrous sodium carbonate was 0.480 mol, and the glucose monohydrate was 14.6 g, accounting for 7% of the theoretical product mass.
[0088] S3, Grinding and Spray Drying: Same as in Example 1.
[0089] S4, Calcination: The precursor is placed in a tube furnace and protected by argon gas. The temperature is increased and calcined according to the following procedure: the temperature is increased to 300℃ at 1.5℃ / min and held for 1 hour, then the temperature is increased to 530℃ at 2.5℃ / min and held for 4 hours. After the holding period, the material is naturally cooled and discharged to obtain carbon-coated iron pyrophosphate sodium.
[0090] Example 4 This embodiment provides an integrated preparation method for high-purity carbon-coated iron pyrophosphate sodium, which differs from Example 2 only in that the organophosphonic acid used is aminotrimethylenephosphonic acid (ATMP).
[0091] Example 5 This embodiment provides an integrated preparation method for high-purity carbon-coated iron sodium pyrophosphate. The only difference from Embodiment 2 is that pyrophosphate is used as the pyrophosphate source instead of sodium pyrophosphate.
[0092] Comparative Example 1 This comparative example uses a conventional two-step method to prepare carbon-coated iron pyrophosphate sodium, specifically including: Using the same wet filter cake of ferric phosphate as in Example 2, it was dried at 120°C for 4 hours and pre-calcined at 600°C for 2 hours to obtain anhydrous ferric phosphate powder. The remaining raw materials and molar ratios were the same as in Example 2. A slurry was prepared and then subjected to grinding, spray drying, and calcination in sequence. The calcination process was as follows: the temperature was increased to 300°C at 1.5°C / min and held for 1 hour, and then increased to 620°C at 3°C / min and held for 8 hours. The remaining parameters were the same as in Example 2.
[0093] Comparative Example 2 The only difference between this comparative example and Example 2 is that no organophosphonic acid and pyrophosphate are added, the calcination temperature is 620°C, and the holding time is 8 hours; the other raw materials and their molar ratios are the same as in Example 2.
[0094] Comparative Example 3 The only difference between this comparative example and Example 2 is that it does not contain organophosphonic acid and pyrophosphate.
[0095] Comparative Example 4 The only difference between this comparative example and Example 2 is that no organic phosphoric acid is added.
[0096] The carbon-coated iron pyrophosphate prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to the following tests, and the test results are shown in Table 1.
[0097] (1) Proportion of impurity phases: Selective mild leaching combined with inductively coupled plasma optical emission spectrometry (ICP-OES) was used for quantitative determination. NaFePO4 and iron oxide impurity phases in the sample were selectively leached using an acetate-sodium acetate buffer solution at pH=3.0. The amount of sodium iron pyrophosphate matrix dissolved was negligible. The iron concentration in the leachate was determined by ICP-OES, and the amount of iron in the impurity phases was calculated to obtain the total molar proportion of the impurity phases.
[0098] (2) Calcination relative energy consumption statistics method: Taking the comprehensive heat and electricity consumption of the unit mass carbon-coated iron sodium pyrophosphate product prepared by the conventional two-step method in Comparative Example 1 as the benchmark of 100%, the energy consumption of each example and comparative example from raw material feeding to carbon-coated iron sodium pyrophosphate product discharge during the drying and calcination process was statistically analyzed, and the relative energy consumption was obtained by comparing with the benchmark.
[0099] The carbon-coated sodium iron pyrophosphate prepared in Examples 1-5 and Comparative Examples 1-4 were used as positive electrode materials to assemble coin-type sodium-ion batteries. Specifically, the positive electrode material, acetylene black, and PVDF were weighed and mixed at a mass ratio of 8:1:1, and N2 was added. The methylpyrrolidone solution (NMP) was homogenized, and then the slurry was uniformly coated onto aluminum foil. It was dried in a vacuum drying oven at 80°C for 6 hours. The positive electrode was obtained by rolling and cutting (14 mm in diameter). A sodium metal sheet was used as the counter electrode. 1 mol / L NaClO4 was used as the electrolyte. The electrolyte was 1 M sodium perchlorate (NaClO4) dissolved in a 1:1 volume ratio ethylene carbonate / propylene carbonate (EC / PC) system, with 5 wt% fluoroethylene carbonate (FEC) added. The separator was a glass fiber membrane. The cells were assembled into a 2032 button cell in an argon-filled glove box.
[0100] The sodium-ion batteries prepared by carbon-coated sodium iron pyrophosphate in each embodiment and comparative example were subjected to the following performance tests, and the test results are shown in Table 1.
[0101] (1) 0.1C discharge specific capacity: With a current density of 0.1C, constant current charging and discharging are performed in the voltage range of 1.5~3.8V. The first charge specific capacity and discharge specific capacity are measured, and the first week coulombic efficiency is calculated as: first discharge specific capacity / first charge specific capacity.
[0102] (2) 10C discharge specific capacity: The discharge specific capacity was measured by charging and discharging at a current density of 10C within a voltage range of 1.5~3.8V.
[0103] (3) Cyclic stability: 1000 cycles of charge and discharge at a current density of 1C within a voltage range of 1.5~3.8V, record the discharge specific capacity at different cycle counts, and calculate the capacity retention rate after 1000 cycles.
[0104] Table 1. Test results of carbon-coated NFPP in each embodiment and comparative example.
[0105] Comparing Example 2 and Comparative Example 1, it can be seen that the preparation method of the present invention reduces the overall energy consumption by 43% compared with the traditional two-step method, increases the purity of the main phase by 3.56%, and increases the first-week coulombic efficiency by 9 percentage points, thus achieving dual optimization of cost and performance.
[0106] Example 2 achieved bidirectional enhancement of crystal phase induction and phosphorus compensation by introducing organophosphonic acid, resulting in a 92% reduction in the content of surface impurity phases compared to Comparative Example 1.
[0107] Comparative Example 3, without the addition of organophosphonic acid and pyrophosphate, showed a high impurity phase ratio of 7.9%, a sharp decline in electrochemical performance, and calcination energy consumption reaching 100% of the baseline value, directly demonstrating the overall necessity of the synergistic modification system of organophosphonic acid and pyrophosphate.
[0108] Comparative Example 4 retains only pyrophosphate and omits organophosphonic acid. Although its performance is improved compared to Comparative Example 3, the proportion of impurity phase, rate performance, cycle stability and calcination energy consumption are significantly different from those of Example 2. This further confirms that organophosphonic acid has an irreplaceable independent role in particle dispersion and anchoring, inhibiting impurity phase formation, reducing sintering energy consumption and constructing a uniform carbon coating layer. The combination of the two produced an unexpected synergistic effect.
[0109] Examples 1-5, using different types and amounts of organophosphonic acids and pyrophosphates, as well as different calcination process parameters, all achieved improved purity of carbon-coated iron pyrophosphate sodium, and the sodium-ion batteries exhibited excellent performance. This demonstrates that the preparation method of the embodiments of the present invention has a wide process window and is suitable for industrial mass production requirements.
[0110] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. An integrated preparation method for high-purity carbon-coated iron sodium pyrophosphate, characterized in that, include: S1, preparing ferric phosphate wet filter cake; S2, preparing the slurry: the ferric phosphate wet filter cake is dispersed in a solvent to form a slurry; an organophosphonic acid is added to the slurry; a pyrophosphate source is then added to the slurry; a phosphorus source, a sodium source, and a carbon source are then added to the slurry to obtain a uniform mixed slurry; S3, spray dry the mixed slurry to obtain the precursor; S4, the precursor is calcined under an inert atmosphere to obtain carbon-coated iron pyrophosphate sodium.
2. The integrated preparation method according to claim 1, characterized in that, The amount of organophosphonic acid added is 0.3wt% to 1.0wt% of the total solid phase mass in the slurry formed by dispersing the ferric phosphate wet filter cake.
3. The integrated preparation method according to claim 1, characterized in that, The organophosphonic acid includes at least one of hydroxyethylidene diphosphonic acid and aminotrimethylene phosphonic acid.
4. The integrated preparation method according to claim 1, characterized in that, The molar amount of the pyrophosphate source is 1% to 3% of the total molar amount of phosphorus in the mixed slurry containing ferric phosphate and phosphorus supplement source.
5. The integrated preparation method according to claim 4, characterized in that, After adding the pyrophosphate source, the pH of the slurry is maintained at 2.0~2.
5.
6. The integrated preparation method according to claim 1, characterized in that, The carbon source includes one or more of glucose and sucrose; And / or, the amount of carbon source added is 5wt% to 10wt% of the final product mass.
7. The integrated preparation method according to claim 1, characterized in that, In step S3, before spray drying the mixed slurry, the mixed slurry is ground until the particle size D50 in the mixed slurry is 0.3~0.5μm.
8. The integrated preparation method according to claim 1, characterized in that, In S4, the calcination includes: First stage: Heat to an intermediate calcination temperature of 280~320℃ and hold for 1~2 hours; Second stage: Continue to heat up to a calcination temperature of 530~560℃ and hold for 4~5 hours.
9. A high-purity carbon-coated iron pyrophosphate sodium salt, characterized in that, It is obtained by the integrated preparation method according to any one of claims 1-8.
10. A sodium-ion battery, characterized in that, The positive electrode material of the sodium-ion battery is high-purity carbon-coated iron pyrophosphate sodium obtained by the integrated preparation method according to any one of claims 1-8.